(untitled) (International Journal of Engineering and Computer Science, 2017)
In ZigBee cluster-tree network, the existing literature works does not provide solution for power efficient scheduling. In addition, the technique to prevent network collision is not explained. In order to overcome these issues, in this paper, we propose Energy Efficient Cluster scheduling for IEEE 802.15.4 Cluster-Tree Network. In this technique, initially, the distributed Pull-Push-Relabel (PPR) algorithm is designed to adapt to a ZigBee cluster-tree network. Then, a time division cluster scheduling technique is considered that offers energy efficiency in the cluster-tree network by maximizing the Cluster Scheduling period in relative to beacon interval. Besides, it prevents resource requirements whereas fulfills some temporal requirements such as end-to-end deadlines of all the flows. By simulation results, we show that the proposed technique reduces the energy consumption and reduces the network collision.